2020
DOI: 10.1063/5.0003961
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of thermal transport in AlxGa1−xAs alloy nanowires with varying compositions

Abstract: Phonon dispersion relations and thermal conductance in AlxGa1−xAs alloy nanowires with varying compositions are investigated. When x varies from 0 to 1, the lowest-energy mode remains almost unchanged, while the cutoff frequency of the high-order modes increases. The thermal conductance of AlxGa1−xAs alloy nanowires is inversely proportional to the Al content x, but proportional to the nanowire width. For a two-terminal GaAs/AlxGa1−xAs/AlAs transport system, it is found that the thermal conductance first decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The third common approach to modulate the thermal conductivity of 2D heterostructres is chemical functionalization. Using SED technology, (Pei et al, 2011;Kim et al, 2012) found that the hydrogenation coverage dependence of thermal conductivity in functionalized graphene shows a U-shaped variation, similar to the composition dependence of thermal conductivity in Si/Ge alloy (Xie et al, 2020). (Mu et al, 2014) reported that a 5% oxidation coverage leads to a 90% reduction of thermal conductivity in graphene samples.…”
Section: From the Perspective Of Phonon-particle Picturementioning
confidence: 78%
“…The third common approach to modulate the thermal conductivity of 2D heterostructres is chemical functionalization. Using SED technology, (Pei et al, 2011;Kim et al, 2012) found that the hydrogenation coverage dependence of thermal conductivity in functionalized graphene shows a U-shaped variation, similar to the composition dependence of thermal conductivity in Si/Ge alloy (Xie et al, 2020). (Mu et al, 2014) reported that a 5% oxidation coverage leads to a 90% reduction of thermal conductivity in graphene samples.…”
Section: From the Perspective Of Phonon-particle Picturementioning
confidence: 78%
“…where A is the cross-sectional area of the unit cell, T L and T R is the temperature of left and right lead, respectively. Ξ ph (ω) is phonon transmission function given by equation (7). By using phonon NEGF method in combined with DFT calculation, Xiong et al [126] calculated extreme near-field heat transfer between two silica clusters and found that the critical gaps could be divided into three parts (4 Å, 12 Å, 20 Å), which satisfied the decaying power law of d −12 , d −3 and d −6 , respectively, as shown in figure 5(a).…”
Section: Near-field Heat Transfermentioning
confidence: 99%
“…The state-of-the-art semiconductor fabrication technology exhibits the capability of manipulating materials down to atomic level, therefore offering the opportunity to realized versatile 3D nanostructures, such as two-dimensional materials [1][2][3][4][5], nanowires [6,7], nanotube [8,9] and molecular junctions (MJs) [10,11]. It makes the study of thermal transport at the nanoscale is of critical importance for the development of novel nano-electronic devices with feature sizes of devices below than 10 nm [12].…”
Section: Introductionmentioning
confidence: 99%